Оptimization approach to the synthesis of plasma stabilization system in tokamak ITER - Ovsyannikov, D.A.; Zavadskiy, S.V. (Вопросы атомной науки и техники, 2018)
Synthesis of the controller of ITER plasma stabilization system is considered. Stabilization system is based on
tokamak diagnostic measurements, defines the voltages in tokamak coils and has the filtering properties. Known
methods of synthesis of plasma regulators are advanced by the presented optimization approach. It makes possible
to meet the requirements for the dynamics of the stabilization process when considering a set of some arbitrary
plasma drops and disturbances. The proposed approach evaluates the ensemble of transient processes of the closed
object. Based on this estimations it is possible to use wide range of optimization techniques. Розглядається синтез регулятора для системи стабілізації плазми в токамаці ІТЕР. Система стабілізації
заснована на вимірах діагностичної системи токамака, вона задає напруги в керуючих котушках і має властивості фільтрації. Відомі методи синтезу регуляторів плазми вдосконалені запропонованим оптимізаційним
підходом. Це дає можливість задовольнити вимоги до якості динаміки процесу стабілізації з урахуванням
різних невизначеностей в динаміці плазми, в тому числі збурень плазми. Запропонований підхід оцінює ансамбль перехідних процесів замкнутого об'єкта. На основі запропонованих оцінок можна використовувати
широкий спектр методів оптимізації. Рассматривается синтез регулятора для системы стабилизации плазмы в токамаке ИТЭР. Система стабилизации основана на измерениях диагностической системы токамака, она задаёт напряжения в управляющих катушках и обладает свойствами фильтрации. Известные методы синтеза регуляторов плазмы усовершенствованы предлагаемым оптимизационным подходом. Это дает возможность удовлетворить требования
к качеству динамики процесса стабилизации с учётом различных неопределённостей в динамике плазмы, в
том числе возмущений плазмы. Предложенный подход оценивает ансамбль переходных процессов замкнутого объекта. На основе предложенных оценок можно использовать широкий спектр методов оптимизации.